2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319956
|View full text |Cite
|
Sign up to set email alerts
|

Automated information extraction from free-text EEG reports

Abstract: In this study we have developed a supervised learning to automatically detect with high accuracy EEG reports that describe seizures and epileptiform discharges. We manually labeled 3,277 documents as describing one or more seizures vs no seizures, and as describing epileptiform discharges vs no epileptiform discharges. We then used Naïve Bayes to develop a system able to automatically classify EEG reports into these categories. Our system consisted of normalization techniques, extraction of key sentences, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Connolly et al examined progress notes for pediatric patients with focal, generalized, or otherwise unspecified epilepsies, analyzing frequencies of word strings using an SVM classifier; after training on 90 notes of each category from one institution, the algorithm demonstrated better‐than‐chance classification of progress notes from a different institution, with improved performance if the classifier was trained using notes from two institutions before being tested on notes from a third . Biswal et al, in contrast, trained a Naïve Bayes classifier on 3277 EEG reports labeled with the presence or absence of seizures or epileptiform discharges, which then achieved an AUC of 99.05% for detecting reports with seizures and 96.15% for those with epileptiform discharges on a testing set of 39 695 reports . Building on this approach, Goodwin and Harabagiu combined automated indexing of EEG reports with neural network‐generated ”fingerprints” of the associated recordings to create a searchable database, allowing for identification of patient cohorts within the database with such queries as, “History of seizures and EEG with TIRDA without sharps, spikes, or electrographic seizures”; a panel of expert reviewers found that the addition of EEG “fingerprint” indices provided more relevant results and captured pertinent records not recovered by searches of EEG reports alone .…”
Section: Machine Learning In the Diagnosis Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Connolly et al examined progress notes for pediatric patients with focal, generalized, or otherwise unspecified epilepsies, analyzing frequencies of word strings using an SVM classifier; after training on 90 notes of each category from one institution, the algorithm demonstrated better‐than‐chance classification of progress notes from a different institution, with improved performance if the classifier was trained using notes from two institutions before being tested on notes from a third . Biswal et al, in contrast, trained a Naïve Bayes classifier on 3277 EEG reports labeled with the presence or absence of seizures or epileptiform discharges, which then achieved an AUC of 99.05% for detecting reports with seizures and 96.15% for those with epileptiform discharges on a testing set of 39 695 reports . Building on this approach, Goodwin and Harabagiu combined automated indexing of EEG reports with neural network‐generated ”fingerprints” of the associated recordings to create a searchable database, allowing for identification of patient cohorts within the database with such queries as, “History of seizures and EEG with TIRDA without sharps, spikes, or electrographic seizures”; a panel of expert reviewers found that the addition of EEG “fingerprint” indices provided more relevant results and captured pertinent records not recovered by searches of EEG reports alone .…”
Section: Machine Learning In the Diagnosis Of Epilepsymentioning
confidence: 99%
“…59 Biswal et al, in contrast, trained a Naïve Bayes classifier on 3277 EEG reports labeled with the presence or absence of seizures or epileptiform discharges, which then achieved an AUC of 99.05% for detecting reports with seizures and 96.15% for those with epileptiform discharges on a testing set of 39 695 reports. 60 Building on this approach, Goodwin and Harabagiu combined automated indexing of EEG reports with neural network-generated "fingerprints" of the associated recordings to create a searchable database, allowing for identification of patient cohorts within the database with such queries as, "History of seizures and EEG with TIRDA without sharps, spikes, or electrographic seizures" 61 ; a panel of expert reviewers found that the addition of EEG "fingerprint" indices provided more relevant results and captured pertinent records not recovered by searches of EEG reports alone. 61 The broad range of data sources examined in these studies highlights the utility of machine learning techniques in leveraging underutilized clinical data for patient-and populationlevel characterization of epilepsy.…”
Section: Nonimaging Diagnosticsmentioning
confidence: 99%
“…Biswal et al achieved an AUC of 0.99 for detecting reports with seizures and AUC of 0.96 for epileptiform discharges, but a limitation of their study is that they did not differentiate focal from generalized findings. [36]…”
Section: Resultsmentioning
confidence: 99%
“…Biswal et al achieved an AUC of 0.99 for detecting reports with seizures and AUC of 0.96 for epileptiform discharges, but a limitation of their study is that they did not differentiate focal from generalized findings. [36] Bao reported 94% accuracy in interictal EEG diagnosis from raw EEG signal. However, this does not improve on the accuracy obtained from structured fields and unstructured reports, and increases the computational resources required for analysis as well as the administrative cost to obtain the raw EEG signal data.…”
Section: Prior Eeg Abnormalitiesmentioning
confidence: 99%
“…In addition to direct analysis of raw EEG signal, EEG abnormalities can be captured by means of structured fields and unstructured reports. Biswal et al achieved an AUC of 0.99 for detecting reports with seizures and AUC of 0.96 for epileptiform discharges, but they did not differentiate focal from generalized findings [36].…”
Section: Prior Eeg Abnormalitiesmentioning
confidence: 99%